2003
DOI: 10.1345/aph.1d154
|View full text |Cite
|
Sign up to set email alerts
|

Memory Loss in a Patient Treated with Fluoxetine

Abstract: Clinicians should be aware of the possible effects of fluoxetine (and possibly other SSRIs) on memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
15
1
Order By: Relevance
“…Our findings might have some relevance to approaches relying upon the modification of serotonergic functions in the brain for treating disorders such as e.g., depression, anxiety, or post-traumatic stress. Concerning depression, for instance, selective serotonin reuptake inhibitors (SSRI) have the best safety record among the different therapeutic options (van Laar et al, 2002), but there is a literature reporting on possible SSRI-related memory problems (Goodnick and Goldstein, 1998;Joss et al, 2003;Wadsworth et al, 2005). Although these memory problems could be related to various confounding factors (subject's history, age, existence of age-related cognitive dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings might have some relevance to approaches relying upon the modification of serotonergic functions in the brain for treating disorders such as e.g., depression, anxiety, or post-traumatic stress. Concerning depression, for instance, selective serotonin reuptake inhibitors (SSRI) have the best safety record among the different therapeutic options (van Laar et al, 2002), but there is a literature reporting on possible SSRI-related memory problems (Goodnick and Goldstein, 1998;Joss et al, 2003;Wadsworth et al, 2005). Although these memory problems could be related to various confounding factors (subject's history, age, existence of age-related cognitive dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Both beneficial (Levkovitz et al, 2002;Harmer et al, 2004;Zobel et al, 2004) and detrimental (Masand and Gupta, 1999;Schmitt et al, 2001;Joss et al, 2003) effects have been reported. In part, this may be due to the differing pharmacological, and hence specific cognitive effects, or individual SSRIs Goodnick and Goldstein, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Most of those who took part reported taking fluoxetine (n ¼ 6), followed by escitalopram (n ¼ 4), citalopram (n ¼ 3), paroxetine (n ¼ 2) and sertraline (n ¼ 2). Fluoxetine has been implicated in memory impairment before (Mirow, 1991;Bradley and Kulik, 1993;Bangs et al, 1995;Joss et al, 2003), as has paroxetine (Furlan et al, 2001;Schmitt et al, 2001), which has anticholinergic properties Schmitt et al, 2001). Both have also been associated with memory improvement (Fudge et al, 1990;Nebes et al, 1990;Tarangano et al, 1997;Cassano et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the suggestion of "cognitive" impairment suggests too broad of an impact. In reality, positive findings along this front have merely suggested memory problems associated with SSRIs and SRNIs (Joss, Burton, & Keller, 2003). In terms of this link with specific SSRIs and/or SNRIs, fluoxetine (Prozac; Joss et al, 2003) and paroxetine (Paxil; Furlan et al, 2001) represent those previously associated with memory impairments, yet they have also been linked with memory improvement (Schmitt, Jorissen, & Sobczak, 2001).…”
Section: Ssris and Snrismentioning
confidence: 99%